ANALISIS FAKTOR RISIKO KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT PADA ANAK BALITA - Asriati Asriati; Zamrud Zamrud; Dewi Febrianty Kalenggo (Halu Oleo University, 2014)
Acute Respiratory Infections (ARI) is one of health problems that exist in developing and developed countries, and a major cause of morbidity and mortality in toddlers. The existence of ARI is influenced by environmental conditions, the availability and effectiveness of health care and preventive measures to prevent the spread of infection, host factor (such as age, smoking habits, ability infectious host, immunity status, nutritional status, prior infection or simultaneous infections caused by others pathogen, general health conditions) and the characteristics of pathogen. The aim of this research is to identify and analyze the risk factor of ARI in toddlers at working area of Public Health Center Jati Raya In Kendari Municipality 2012. This research is an analytic observational with case control design. The sample in the research were 68 case respondents and 68 control respondents taken by using purposive sampling, the respondent is the toddler’s mother. Data is collected from August to October 2012 at working area of Public Health Center Jati Raya In Kendari Municipality by conducting interview through questionnaire. Data is analyzed by using odds ratio statistic test and presented in form of univariate and bivariate table. The result of this research show that the density of dwelling house (OR=3,596) and smoke exposure (OR=7,8) are the risk factor for the existence of ARI in toddlers, while exclusive breastfeeding is a protective factor for the existence of ARI in toddlers.From these result it could be concluded that the density of dwelling house and smoke exposure are the risk factor exclusive breastfeeding is a protective factor for the existence of ARI in toddlers at working area of Public Health Center Jati Raya In Kendari Municipality 2012.Key Words: ARI, density of dwelling house, smoke exposure, exclusive breastfeeding